FORMULATION AND EVALUATION OF MONTELUKAST SODIUM AND LEVOCETIRIZINE DIHYDROCHLORIDE SUBLINGUAL TABLETS - k, SWAPNA; c, APARNA; SRINIVAS, PRATHIMA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: The objective of the current study was to develop and optimize sublingual tablets of montelukast sodium and levocetirizine dihydrochloride which are effective drugs in the treatment of asthma. Methods: The sublingual tablets of montelukast sodium and levocetirizine dihydrochloride were prepared by direct compression method using sodium starch glycolate, crospovidone (CP), and croscarmellose sodium (CCS) as superdisintegrants. The tablets were evaluated for physical properties including hardness, weight variation, thickness, friability, drug content, wetting time, water absorption ratio, in vitro disintegration time, and in vitro dissolution study. Results: The hardness, weight variation, thickness, friability, and drug content of tablets were within pharmacopoeial limits. An optimized tablet formulation F8 was found to have short wetting time of 18.36 seconds, water absorption ratio of 94.42 and in-vitro disintegration time of 45.42 seconds. The results indicated that the amount of super disintegrants such as CP and CCS significantly affected the dependent variables like wetting time, water absorption ratio and in-vitro disintegration time. The in-vitro drug release was found to be higher for formulation F8 with 94.59% for montelukast sodium and 95.48% for levocetirizine dihydrochloride within 60 minutes. The drug release improved by 1.88 times for montelukast sodium and 1.82 times for levocetirizine dihydrochloride compared to oral marketed immediate release tablet formulation. Conclusion: From the present study, it can be concluded that sublingual route has potential to improve the bioavailability of the drug by avoiding first pass metabolism, to provide quicker onset of action and to improve patient compliance in the management of asthma. Keywords: Sublingual tablet, Montelukast Sodium, Levocetirizine Dihydrochloride, In vitro dissolution study.